Submaximal markers of fatigue and overreaching; Implications for monitoring athletes - Siegl, A.; Kösel, E. M.; Tam, N.; Koschnick, S.; Langerak, N. G.; Skorski, S.; Meyer, T.; Lamberts, R. P. (International Journal of Sports Medicine, 2017)
The regular monitoring of athletes is important to fine-tune training and detect early symptoms of overreaching. Therefore the aim of this study was to determine if a noninvasive submaximal running test could reflect a state of overreaching. 14 trained runners completed a noninvasive Lamberts Submaximal Running Test, one week before and 2 days after finishing an ultramarathon, and delayed onset of muscle soreness and the daily analysis of life demands for athletes questionnaire were also captured. After the ultramarathon, submaximal heart rate was lower at 70% (-3 beats) and 85% of peak treadmill running speed (P<0.01). Ratings of perceived exertion were higher at 60% (2 units) and 85% (one unit) of peak treadmill running speed, while 60-second heart rate recovery was significantly faster (7 beats, P<0.001). Delayed Onset of Muscle Soreness scores and the number of symptoms of stress (Daily Analysis of Life Demands for Athletes) were also higher after the ultramarathon (P<0.01). The current study shows that the Lamberts Submaximal Running Test is able to reflect early symptoms of overreaching. Responses to acute fatigue and overreaching were characterized by counterintuitive responses, such as lower submaximal heart rates and faster heart rate recovery, while ratings of perceived exertion were higher.